Fenoterol Enantiomers do not Possess Beneficial Therapeutic Properties of Their Racemic Mixture in the Rat Model of Post Myocardial Infarction Dilated Cardiomyopathy - Ahmet, Ismayil (Cardiovasc Drugs Ther, 2012)
PURPOSE: A salutary effect of β(2) adrenergic receptor (AR) agonist, fenoterol has been demonstrated in a rat model of post-myocardial infarction (MI) dilated cardiomyopathy (DCM). Recent reports on single cardiomyocyte experiments suggested that out of two enantiomers, RR and SS, that constitute a racemic mixture of fenoterol, only RR-enantiomer is an active component that might be a promising new drug for treatment of chronic heart failure. The objective of this study was to compare the efficacy of the RR enantiomer of fenoterol with efficacy of racemic fenoterol, and SS, an inactive enantiomer, in whole animal experimental models of DCM. METHODS: Two weeks after induction of MI by permanent ligation of the anterior descending coronary artery early cardiac remodeling and MI size were assessed via echocardiography and rats were divided into treatment groups. Treatment (placebo, racemic fenoterol, RR- or SS-enantiomers of fenoterol) continued for 6 months while progression of DCM was followed by serial echocardiography. RESULTS: Compared with untreated rats, rats treated with racemic fenoterol demonstrated previously described attenuation of LV remodeling, functional decline and the arrest of the MI expansion during the first two months of treatment. On the contrary, the treatment with either RR-, or with SS-enantiomers of fenoterol was completely ineffective. CONCLUSION: The conclusion drawn on the basis of previous experiments with single cardiomyocytes that RR-enantiomer of fenoterol represents an active component of racemic fenoterol and can be further investigated as a new drug for treatment of chronic heart failure was not confirmed in the whole animal model of DCM.